KONSEP ILMU MENURUT IBNQAYYIM AL-JAWZIYYAH - Siti Fatonah (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2020)
One of the challenges of contemporary Islamic thought was the secularization of science. As a result, the values of science in Islam changed, both in terms of the meaning of knowledge, tot hegoalofac achieving knowledge. From these problems, this study aimed to provide a solution by presenting the contribution of one of the previous scholars who was competent in the field of science, namely Imam Ibn Qayyimal-Jauziyah. This research included a character study research using a qualitative method, which described and analyzed Ibn Qayyimal-Jauziyah's thought which was related to the concept of science. The data collection was carried out by means of a literature study. The results of this study revealed the view of Ibn Qayyimal-Jawziyyah that science occupied an important position in the teachings of Islam. It was because of science, that humans could achieve perfect happiness. To achieve this happiness, the author found that Ibn Qayyimal-Jawziyyah mentioned the level of knowledge into three parts from the lowest to the highest level. The higher a person reached the level of knowledge, the more happiness he would get. Thus, this study tried to formulate the concept of knowledge expressed in the works of Ibn Qayyimal-Jawziyyah including Miftāh dar al-Sa'adah, Madārijal-Sālikīn. This effort was expected to provide the spirit of Muslims in studying so that they can achieve true and not false happiness.